Squeeze film analysis of three-layered parallel plate and partial journal bearing lubricated with couple stress fluids for skeletal joint applications - Rao, T.V.V.L. (Elsevier Ltd, 2019)
Squeeze film lubrication in surfaces approaching each other with a normal velocity, play an important role in skeletal joints. The objective of this study is to analyse the squeeze film load capacity characteristics of three-layered parallel plate and partial journal bearing lubricated with couple stress fluids for skeletal joint applications using one-dimensional analysis. The nondimensional squeeze film pressure is derived based on modified Reynolds equation. The couple stress fluids take into account of lubricant properties with additives are analyzed based on Stokes micro-continuum theory. The Brinkman model is utilized to model the flow in the porous region. In this work, bearing performance improvement under the influence of lubricants with additives are evaluated using surface (or porous) adsorbent layer on stationary plate (or bearing), couple stress fluid film core region, and surface adsorbent layer on moving plate (or journal). The nondimensional squeeze film load capacity increases with (i) increase in couple stress effects, (ii) increase in dynamic viscosity ratio of surface to core layer, and (iii) decrease in permeability of porous layer. The surface (or porous) adsorbent layer and couple stress fluid film core layer improve the squeeze film bearing characteristics for skeletal joints. Â© 2019 Elsevier Ltd. All rights reserved.